Penerapan Primum Remedium Terhadap Pelaku Eksploitasi Benih Bening Lobster Secara Ilegal - Dean Ezekiel Surbakti; Erna Dewi; Maya Shafira; Muhammad Farid; Siti Azizah (CV. ITTC INDONESIA, 2026)
Illegal exploitation of clear lobster seeds (BBL) is a form of fisheries crime that has an impact on the sustainability of marine resources and causes economic losses for the state. The high demand for the international market and the economic value of BBL encourage the rampant practice of illegal trade carried out in an organized manner. This study aims to analyze legal arrangements related to the management and protection of clear lobster seeds, examine the modus operandi of perpetrators of illegal exploitation of BBL, and analyze the application of the principle of primum remedium in court decisions related to these criminal acts. The research method used is normative legal research with a statutory approach and a case approach through the analysis of the Tanjung Karang District Court Decision Number 796/Pid.Sus/2024/PN Tjk and the Pacitan District Court Decision Number 34/Pid.Sus/2025/PN Pct. The results of the study show that Indonesia already has a strong legal basis in the management and protection of BBL, both through international legal instruments and national regulations. The modus operandi of BBL exploitation is carried out systematically through the stages of illegal collection, packaging, transportation, and distribution involving an organized network. The application of the principle of primum remedium can be seen through the use of criminal law as the main instrument in overcoming fisheries crimes. However, law enforcement still tends to target lower-level perpetrators and is not optimal in dismantling intellectual actors or the main controllers of illegal networks. Therefore, a more integrated law enforcement policy is needed so that the application of the primum remedium principle can be effective in protecting fishery resources and maintaining the sustainability of Indonesia's marine ecosystem.